Maternal cortisol level around conception is associated with offspring sex ratio in captive European wild rabbit (Oryctolagus cuniculus) - Benedek, Ildikó; Altbäcker, Vilmos; Zsolnai, Attila; Molnár, Tamás (Acta Agraria Kaposváriensis, 2022)
The sex ratio of the offspring at birth is usually 1: 1 established by natural selection. The sex allocation model predicts that if parents have adequate resources, they would benefit from differentially allocating maternal investment to that sex having higher fittness under the particular environmental conditions. However, little is known about what mechanisms would result in biased sex ratio. One such mechanism could be the interaction of of stress reactivity and progesterone levels in the mothers around conception. In the present investigation the fecal cortisol and progesterone levels at the day of conception were measured in fifteen European wild rabbit does kept in cages. The does were clustered to low and high cortisol response groups and the sex ratio of their progeny was determined. We found a significant correlation between the progesterone levels of mothers and their stress status measured at the mating. This correlation was also reflected in the sex ratio bias in their litters. Even though the litter size was not different, we found higher progesterone levels and more female offspring in the does with higher cortisol levels indicating that maternal status around conception may affect the litter sex ratio.
Keywords: sex allocation; stress; progesterone; glucocorticoids; faecal cortisol